HOME OFFICE MANAGEMENT ACTION PLAN USING THE ISM METHOD - LIU, ZHI JIAN; Edison C. Sembiring; Maya Diah Dewi Maharani (Fakultas Ekonomi Universitas Kadiri, 2024)
The increasing number of remote workers, especially in response to global challenges such as the COVID-19 pandemic, has demonstrated the importance of using an effective home office management approach. Technological infrastructure, communication dynamics, employee productivity, and work-life balance are key components that influence home office management. Data were collected through interviews, surveys, and focus groups with employees working remotely using a mixed-methods approach. To systematically study the relationships between these elements, the ISM method was used. The result is a hierarchical model that distinguishes between driver and dependent variables. To refine this analysis, a SWOT (Strengths, Weaknesses, Opportunities, and Threats) assessment was conducted to uncover the internal strengths and weaknesses of current home office practices. The research suggests that to successfully manage a home office, an integrated approach must be used to address the structural difficulties and strategic opportunities offered by remote work.